The mediating role of organizational support in improving employee performance influenced by organizational commitment at BPS offices in banten province - Pratama, Bayu (Institute of Computer Science (IOCS), 2024)
This study aims to examine and analyze the mediating role of organizational support in improving employee performance, which is influenced by organizational commitment at BPS offices in Banten Province. Considering the importance of implementing organizational commitment to further improve the performance of BPS employees in Banten Province. The research method uses a quantitative approach with a sample of 175 BPS employees in Banten Province who were collected through questionnaires and data analysis using the SmartPLS 3.2.9 program. The research results show that organizational commitment has a positive and significant effect on employee performance, both directly and mediated by organizational support. The contribution of this research can be used for academic and practical purposes and can be used as a guideline for decision-making of the Head of BPS in Banten Province